Aseptic abscess syndrome: a case report of a patient achieving remission with both infliximab originator and biosimilar administered at varied intervals - Ucci, Federica Maria; Scrivo, Rossana; Alessandri, Cristiano; Conti, Fabrizio; Priori, Roberta (Frontiers in Immunology, 2024)
Aseptic abscesses syndrome is a rare but increasingly recognized disease that falls within the spectrum of autoinflammatory disorders. Here, we describe the case of a patient who presented with abdominal pain and fever, along with multiple abdominal and extra-abdominal abscesses, in the absence of underlying hematologic, autoimmune, infectious, or neoplastic conditions. Initially, the patient responded to glucocorticoids, but experienced several flares upon discontinuation, leading to the initiation of treatment with a TNFα inhibitor. After 5 years, an attempt to discontinue treatment resulted in a new flare of the disease. Remission was eventually achieved with a biosimilar TNFα inhibitor, albeit requiring shortened infusion intervals.